An enhanced dispersive liquid–liquid microextraction method based on solidification of floating organic drops for the determination of pyrethroid pesticides in tea infusions. (16th February 2022) - Ju, Ziwei; Qian, Heng; Pan, Nianyou; Huang, Yuting; Xu, Qinqin; Yan, Chen; Zhou, Wenfeng
Abstract : A novel enhanced dispersive liquid–liquid microextraction method based on solidified floating organic solvents containing [P4, 4, 4, 12 ][PF6 ] and a hydrophobic solvent mixture for the determination of four pyrethroid insecticides in tea infusions. Abstract : In this study, a novel enhanced dispersive liquid–liquid microextraction method was developed for the determination of four pyrethroid insecticides (deltamethrin, etofenprox, bifenthrin and fenpropathrin) in tea infusions, based on solidified floating organic solvents containing [P4, 4, 4, 12 ][PF6 ] generated in situ and a hydrophobic mixture of 1-chlorododecane and 1-dodecanol. Both the hydrophobic mixture and [P4, 4, 4, 12 ][PF6 ] were used as extractants in this method. Several key factors, such as the solvent mixture dosage, the molar ratio of [P4, 4, 4, 12 ]Br to KPF6, the reaction temperature and the added salt concentration, that affected the recovery were optimized. According to the results of spiked recovery experiments under optimized conditions, the recoveries of all four pyrethroid pesticides ranged from 81.2% to 103.7%, with relative standard deviation (RSD) values ranging from 2.2% to 5.1%. The limit of detection (LOD) values for deltamethrin, etofenprox, bifenthrin and fenpropathrin were 0.39 μg L −1, 0.47 μg L −1, 0.42 μg L −1 and 0.68 μg L −1, respectively. This method fully utilizes the advantageous characteristics of ionic liquids (ILs) and adds the extractant mixture simultaneously to the IL, making the whole experimental process environmentally friendly, efficient, simple and fast. Overall, this is an effective method for the detection of pyrethroid pesticide residues in tea infusions.